Everybody Wins The Lottery - Ho, Jonathan Hee Weng (Nanyang Technological University, 2022)
EVERYBODY WINS THE LOTTERY is an alternative comedy film as part of our team’s undergraduate Final Year Project in Wee Kim Wee School of Communications and Information at Nanyang Technological University. The team consists of Jonathan Ho Hee Weng (Producer), Fontanilla Eryka Base Joyce & Yang Sheng Xiong (Co-Directors), and Bryan Tan Yong Ern (Director of Photography), under the supervision of Professor Kym Campbell. This report documents the filmmaking process and insights to the above mentioned film.